Fashion Designer Behavior Toward Eco-Fashion Design - Marzie Hatef Jalil; Siti Shukhaila Shaharuddin (ITB Journal Publisher, LPPM ITB, 2020)
An important aspect of the future of fashion design is eco-fashion. The first aim of this study was to understand how personal attitude affects fashion designers in pursuing eco-fashion design in their work. Secondly, the designer's behavior toward eco-fashion design was investigated. This study applied the theory of reasoned action (TRA) as the foundation for understanding the designers' behavior. A mixed-method two-stage solution was used. Data were collected through qualitative open-ended questions distributed among eight sustainable fashion designers and 98 fashion designers who were selected as the research subjects for a survey. Direct logistic regression and MANOVA were applied for statistical analysis. The model was tested via structural equation modeling (PLS-SEM). The most important ï¬ndings of the research were that a positive attitude toward eco-fashion design could predict the designer's intention toward sustainability better than social norms. Further, the participants confirmed that environmental knowledge, perceived quality and price, perceived functional and aesthetic values, and the perceived usefulness of technology in the application of eco-fashion materials affected their attitude towards eco-fashion design. Furthermore, corresponding policies are proposed to facilitate clothing waste minimization in design through the use of eco-fashion materials, which could gain widespread attention and become a new trend in fashion.